Pengenalan Investasi dan Perencanaan Keuangan Jangka Panjang Bagi Masyarakat Desa Kwala Serapuh Kabupaten Langkat - Noni Ardian; Chaerul Rizky; Angelina Br. Capah (Journal of Social Responsibility Projects by Higher Education Forum, 2023)
Introduction to investment and long-term financial planning is important for the community, especially for rural communities. This is because rural communities generally have limited income, so they need to manage their finances well in order to achieve their financial goals. This study aims to introduce investment and long-term financial planning to the people of Kwala Serapuh Village, Langkat Regency. The study was conducted using survey and interview methods. The results of the study showed that the people of Kwala Serapuh Village have a low understanding of investment and long-term financial planning. This is because rural communities generally have low levels of education and limited access to information. Based on the results of the study, it is recommended to increase the understanding of the people of Kwala Serapuh Village about investment and long-term financial planning through various educational and socialization activities.